Pemberdayaan Ibu Rumah Tangga melalui Literasi Manajemen Keuangan untuk Penguatan Usaha Mikro - Suparyati, Agustina; Elyana Amran; Masfar Gazali; Ovy Noviati Nuraini Magetsari (Dirkantara Indonesia, 2025)
Housewives play a strategic role in maintaining household economic resilience, both as family financial managers and as micro-entrepreneurs. This community service program aimed to empower housewives through financial management literacy, particularly in separating family and business finances and preparing simple financial statements. The program was conducted offline in Batu Ampar, East Jakarta, involving 14 housewives who manage micro businesses. The methods used were participatory lectures, interactive discussions, and technical assistance. The evaluation results indicated a significant improvement: before the training, only 35% of participants were able to distinguish between household and business finances, which increased to 85% after the training. In addition, 80% of participants were able to independently prepare simple financial reports. This program demonstrates that practice-based financial literacy can enhance housewives’ capacity in managing both family and business finances, thereby strengthening their contribution to household and community economic resilience.